House and Hearth. The Social Setting of Food Preparation in the Western Anatolian and Southeastern European Neolithic - Van Den Bos, Elisha O. (Food & History, 2021)
Abstract This contribution investigates Neolithic communities in Western Anatolia and the southern Balkans (6800-5600 BC) through the settlement context of structures associated with food preparation, including ovens, hearths, grinding installations and storage facilities. The study area plays a key role in current Neolithization debates, both because of its geographical position between Southwest Asia and Europe and because of a wealth of new field data, which complicate and challenge traditional Neolithization models. I argue that food practices attest regional trajectories of change in the definition of Neolithic ways of life, as well as interactions between regional cultures. Abstract Cet article étudie les communautés néolithiques d’Anatolie occidentale et des Balkans méridionaux (6800-5600 avant J.-C.) à travers l’analyse contextuelle des structures associées à la préparation des aliments, y compris les fours, les foyers, les installations de broyage et les structures de stockage. La zone d’étude joue un rôle clé dans les débats actuels sur la néolithisation, non seulement de par sa position géographique entre l’Asie du Sud- Ouest et l’Europe, mais aussi par la richesse des nouvelles données de terrain qui remettent en question les modèles de néolithisation traditionnels. Je soutiens l’idée que les pratiques alimentaires attestent de trajectoires régionales, de changement dans la définition des modes de vie néolithiques, ainsi que des interactions entre les cultures régionales.